1990
DOI: 10.1038/hdy.1990.75
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome location of genes controlling tolerance to salt (NaCl) and vigour in Hordeum vulgare and H. chilense

Abstract: Wheat/Hordeum vulgare and wheat/H. chilense disomic chromosome addition lines have been used to locate genes influencing tolerance to salt to specific chromosomes of the H and Hd genomes of H. vulgare and H. chilense respectively. The addition lines were grown in hydroculture containing either 0 mol m3, 175 mol m3 or 200 mol m3 sodium chloride. Various growth and yield parameters were measured and comparisons were made both between species and between chromosomes. Nat vigour was found to have a major effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 15 publications
1
56
1
Order By: Relevance
“…and K ? contents in the leaves during salt stress, while Forster et al (1990) found that barley chromosomes 4H and 5H had a positive effect on salt tolerance on the basis of growth parameters and yield components. The salt-tolerance of sea barleygrass (H. marinum), an extremely salt-tolerant species, was expressed in wheat-sea barleygrass (CS-H21) amphiploids (Islam et al 2007) and the additive or interactive actions of chromosomes Hm2, Hm6 and Hm7 were observed in their addition lines (Raffi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…and K ? contents in the leaves during salt stress, while Forster et al (1990) found that barley chromosomes 4H and 5H had a positive effect on salt tolerance on the basis of growth parameters and yield components. The salt-tolerance of sea barleygrass (H. marinum), an extremely salt-tolerant species, was expressed in wheat-sea barleygrass (CS-H21) amphiploids (Islam et al 2007) and the additive or interactive actions of chromosomes Hm2, Hm6 and Hm7 were observed in their addition lines (Raffi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Naturally evolved salt tolerance is a quantitative and polygenic trait associated with numerous morphological and biochemical adaptations (Shannon 1984(Shannon , 1985Tal 1984Tal , 1985Epstein and Rains 1987;Cushman et al 1989). The level of genetic complexity is evidenced by the multigenic inheritance, e.g., various heritabilities, of salt tolerance traits in such taxa as rice (Yeo et al 1988), barley (Forster et al 1990), tomato (Saranga et al 1992), various grass species (Ashrafet al 1986), pigeonpea (Subbarao et al 1990), and wheat (Schachtman and Munns 1992). In the Triticaceae, responses to salt of chromosome addition lines from Thinopyrum elongatum into tetraploid (Triticum durum cv Stewart) or hexaploid wheat (Triticum aestivum Chinese Spring) show that several chromosomes may contribute to Na+ exclusion, distinct from the K+/Na+ discrimination trait controlled by Knal in the D genome of wheat (Gorham 1994).…”
Section: Genetic Complexity Of Salt Tolerancementioning
confidence: 99%
“…The tests involved growing plants in hydroculture with or without the addition of salt (NaC1). The technique was essentially that described by Forster et al (1990) with the following amendments: single grains were germinated in 10 cmx 1.5 cm (diameter) tubes (Sarstedt) filled with vermiculite. These were suspended in hydroculture tanks so that the seed lay 1 cm above the hydroculture solution and 5 cm from the bottom of the tube.…”
Section: Sodium Accumulation Testsmentioning
confidence: 99%